Theoretical analysis of the non-reciprocal phase shifts due to birefringence and topology in fiber ring interferometers. (October 2021) - Liu, Junhao; Xu, Tianhua
Highlights: Correct Jones matrix of the fiber coil for backward propagation was given. Non-reciprocal phase shifts induced by the linear and circular birefringence of the coiled fiber were derived. Performance of fiber ring interferoremters were strongly limited by the fabricaiton. Abstract: The non-reciprocal phase shifts in fiber ring interferometers due to the fiber birefringence and the path topology are investigated for the first time. It is shown that the resultant birefringence of the fiber, which is the combination of the linear birefringence intrinsic to the fiber and the circular birefringence induced by the twisting in the fiber coiling, is not reciprocal for both rays in the bidirectional propagation due to the path topology confined by the coiled fiber. Our model indicates that the performance of fiber ring interferometers periodically depends on both the linear and the circular birefringence of the coiled fiber, and the bias error can be reduced by the typical fabrication process of the fiber ring interferometers.